Oceans as bioenergy pools for methane production using activated methanogens in waste sewage sludge. (15th September 2017) - Mohd Yasin, Nazlina Haiza; Ikegami, Azusa; Wood, Thomas K.; Yu, Chang-Ping; Haruyama, Tetsuya; Takriff, Mohd Sobri; Maeda, Toshinari
Graphical abstract: Highlights: CO2 dissolved in seawater can be a carbon source for methane production. Methane energy was generated from seawater (carbonate ion) by enriched methanogens. Microbial communities adapted to seawater salinity improved methane production. 81% of 13 CH4 was generated from microbial conversion of NaH 13 CO3 . Abstract: The dissolved CO2 that causes ocean acidification has great potential for bioenergy production. In this study, we demonstrate that activated methanogens in waste sewage sludge (WSS) are useful for converting bicarbonate in seawater into methane. These activated methanogens were adapted in different seawater sources for methane production through repeated batch experiments that resulted in an increase of 300–400 fold in the methane yield. During these repeated batch experiments, the microbial communities in WSS adapted to the high salinity of seawater to generate more methane. Microbial community analysis showed the dominance of Achromobacter xylosoxidans, Serrati sp. and methanogens including Methanobacterium sp., Methanosarcina sp., and Methanosaeta concillii . Using a 13 C-labeled isotope, we demonstrate that 81% of the methane is derived from microbial conversion of NaH 13 CO2 in artificial seawater. Therefore, this study shows that oceans, with the largest surface area on Earth, have a potential as a substrate for methane energy production via an acclimated consortium approach.